Intestinal Type Gastric Cancer and Gastric Adenoma - Cheal Wung Huh; Sang Kil Lee (The Korean Journal of Helicobacter and Upper Gastrointestinal Research)
Gastric adenoma (dysplasia) is a precursor for gastric cancer and is closely associated with intestinal type gastric cancer. Thus, accurate diagnosis and proper management of gastric adenoma are extremely critical for preventing gastric cancer. The revised Vienna and World Health Organization classifications have categorized gastric adenomas into two types: high-grade and low-grade dysplasia. High-grade dysplasia requires endoscopic resection due to synchronous carcinoma or the high risk of progression to carcinoma. Although the treatment for low-grade dysplasia remains controversial, endoscopic resection is also recommended due to the potential of progression to carcinomas and the unrevealed histologic discrepancies between forceps biopsy and endoscopic specimens. According to the Lauren classification, gastric cancer is categorized into three histologic types: intestinal, diffuse, and mixed types. Intestinal and diffuse types show a distinct difference in their clinical and epidemiological features. The intestinal type, in its pathogenesis, follows the cascade of non-atrophic gastritis, atrophic gastritis, intestinal metaplasia, adenoma, and intramucosal neoplasia (correa cascade). It tends to appear in older ages than diffuse type and show some predominance in the distal portion of the stomach. It is more common in males and is often associated with environmental factors. In this review, the current knowledge of gastric adenoma and intestinal type gastric cancer, together with relevant diagnostic and therapeutic strategies, is discussed.